The large plasmid carried class 1 integrons mediated multidrug resistance of foodborne Salmonella Indiana - Wang, Xuefeng; Wang, Tian; Guo, Mengjiao; Zhang, Chengcheng; Bo, Zongyi; Wu, Yantao; Chao, Guoxiang (Frontiers in Microbiology, 2022)
Salmonella Indiana has emerged in recent years as an important zoonotic pathogen. The molecular mechanism of multidrug resistance (MDR) in S. Indiana is not known and should be assessed. We aim to investigate the molecular mechanism of MDR and the importance of large plasmids carried class 1 integrons in the MDR of foodborne S. Indiana. Class 1 integrons in 48 S. Indiana isolates and 200 isolates of 7 other Salmonella serotypes were detected by PCR. To analyze the antimicrobial resistance genes (ARGs) of two S. Indiana isolates, designated S. Indiana 15 and S. Indiana 222, next generation sequencing (NGS) was performed, and the resulting sequences were compared with the complete nucleotide sequences of S. Indiana D90 and S. Indiana C629. Comparative functional analysis was conducted between the intI1 (1014 bp) of S. Indiana 222 and the intI1 (699 bp) of S. Indiana 15. Plasmid conjugation transfer analysis was performed to analyze the horizontal gene transfer of the integrons-related resistance genes with integron-positive and integron-negative Salmonella isolates. 64.58% of S. Indiana carried class 1 integrons, which was significantly higher than that of other Salmonella serotypes (p < 0.001). The NGS results showed that the S. Indiana 15 and S. Indiana 222 isolates carried a large plasmid with a class 1 integron and multiple ARGs, similar to S. Indiana D90 and S. Indiana C629. Two integrases found in S. Indiana isolates belong to class 1 integrases and could integrate resistance genes into specific integration sites of the integrons. The conjugation frequency of intI1 (1014 bp) was 6.08×10-5, which was significantly higher than that of intI1 (699 bp) (p < 0.01). The large plasmids carrying a class 1 integron and the number of ARGs were strongly correlated (p < 0.001). The conjugation frequency of integron-positive S. Indiana recipient isolates was significantly higher than that of integron-negative recipient isolates (p < 0.05). S. Indiana containing large plasmids carrying a class 1 integron more easily captured resistance genes from other bacteria (S. Enteritidis and S. Derby), which could be an important cause of the emerging pandemic of MDR clones.